COVID-19 in Latin America : A High Toll on Lives and Livelihoods - Bakker, Bas (IMF Working Papers; Working Paper ;, 2021)
Latin America was hit hard by Covid-19, both in terms of lives and livelihoods. Early lockdowns in the second quarter of 2020 prevented an explosion of deaths at the time but did not stop the pandemic from later wreaking havoc in the region. This paper investigates the dynamics of pandemics in Latin America and how it differed from elsewhere. We probe the role of non-pharmaceutical interventions; the effectiveness (or lack of thereof) lock-downs in Latin America; which structural factors contributed to the high death toll in Latin America, and the extent to which the epidemic harmed the economy. Finally, we briefly analyze the roots of the second-waves that started in the fourth quarter of 2020.